Association of Age with Efficacy of Immunotherapy in Metastatic Melanoma. (29th October 2019) - Jain, Varsha; Hwang, Wei‐Ting; Venigalla, Sriram; Nead, Kevin T.; Lukens, John N.; Mitchell, Tara C.; Shabason, Jacob E.
Abstract: Management of melanoma has been revolutionized by the use of immune checkpoint inhibitors. Immune system changes associated with aging may affect the efficacy of immune‐based therapies. Using the National Cancer Database, we evaluated the impact of age on the receipt and efficacy of modern immunotherapies in patients with metastatic melanoma. We identified 11, 944 patients from 2011–2015, of whom 25% received immunotherapy. Older (≥60 years), compared with younger, patients were less likely to receive immunotherapy (odds ratio, 0.69; 95% confidence interval [CI], 0.61–0.78; p < .001). Immunotherapy was associated with a survival benefit in both younger and older patients (<60 years: hazard ratio [HR], 0.64; 95% CI, 0.57–0.72; p < .001; ≥60 years: HR, 0.55; 95% CI, 0.50–0.60; p < .001). Importantly, there was a statistically significant interaction between age and survival with immunotherapy, where a greater benefit was observed for older patients ( p interaction = 0.013). Further work studying the age‐related response to immunotherapy is warranted. Abstract : Recent evidence suggests that patient age may have an important effect on patient response to immunotherapies. This article evaluates the effect of age on the receipt and efficacy of modern immunotherapies in patients with metastatic melanoma.